BURIED PLIOCENE CALDERAS IN EASTERN AND SOUTHERN KAMCHATKA - Popruzhenko S.V.; Aprelkov S.E. (My University, 2001)
The morphology of the gravity field and the distribution of Pliocene ignimbrites were analyzed to locate Late Neogene calderas which had been covered by younger volcanic formations.
Keywords: Pliocene; Ignimbrites; Kamchatka; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен